Probing atomic positions of adsorbed ammonia molecules in zeolite. Issue 16 (2nd February 2016) - Ye, Lin; Lo, Benedict T.W.; Qu, Jin; Wilkinson, Ian; Hughes, Tim; Murray, Claire A.; Tang, Chiu C.; Tsang, Shik Chi Edman
Abstract : The atomic positions and interactions between adsorbed guest molecules, such as ammonia in H-ZSM-5 microporous solids, are for the first time revealed by using in situ synchrotron powder X-ray diffraction combined with refinement within experimental errors. Abstract : Atomic positions and interactions between adsorbed guest molecules, such as ammonia in H-ZSM-5 microporous solids, are for the first time revealed by making use of the change in the periodical scattering parameter using in situ synchrotron powder X-ray diffraction combined with refinement within experimental errors.